Unlocking the multifaceted roles of GLP-1: Physiological functions and therapeutic potential - Tohada M. AL-Noshokaty; Rehab Abdelhamid; Nourhan M. Abdelmaksoud; Aya Khaled; Mariam Hossam; Razan Ahmed; Toka Saber; Shahd Khaled; Shereen Saeid Elshaer; Ahmed I. Abulsoud (Toxicology Reports)
Glucagon (GCG) like peptide 1 (GLP-1) has emerged as a powerful player in regulating metabolism and a promising therapeutic target for various chronic diseases. This review delves into the physiological roles of GLP-1, exploring its impact on glucose homeostasis, insulin secretion, and satiety. We examine the compelling evidence supporting GLP-1 receptor agonists (GLP-1RAs) in managing type 2 diabetes (T2D), obesity, and other diseases. The intricate molecular mechanisms underlying GLP-1RAs are explored, including their interactions with pathways like extracellular signal-regulated kinase 1/2 (ERK1/2), activated protein kinase (AMPK), cyclic adenine monophosphate (cAMP), mitogen-activated protein kinase (MAPK), and protein kinase C (PKC). Expanding our understanding, the review investigates the potential role of GLP-1 in cancers. Also, microribonucleic acid (RNA) (miRNAs), critical regulators of gene expression, are introduced as potential modulators of GLP-1 signaling. We delve into the link between miRNAs and T2D obesity and explore specific miRNA examples influencing GLP-1R function. Finally, the review explores the rationale for seeking alternatives to GLP-1RAs and highlights natural products with promising GLP-1 modulatory effects.